ANALYSIS OF EXPRESSIVE UTTERANCES OF STATUSES UPDATE ON SOCIAL MEDIA TWITTER USED BY STUDENTS OF STKIP MUHAMMADIYAH BOGOR - Wawat Srinawati (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Twitter has turned from a niche service to a mass phenomenon. It is an online social networking tool in which users post 140 character updates of what is going on in their lives along with links to things they think are interesting, funny, or useful to their followers. The statuses are human speech acts underwriting. This research aims to describe the linguistic form of expressive utterances and describe the intentions of expressive utterance in status updates on social media Twitter used by students of STKIP Muhammadiyah Bogor. The type of this research is a descriptive qualitative research in which the writer used documentation and observation method as the method of collecting data. The data of this research are written utterances made by students of the English Department in STKIP Muhammadiyah Bogor. A set of questionnaire was given to all the sixth semester of English education in order to assess their attitude and feedback toward the expressive utterances of statues update on social media Twitter. The result of findings from the data of expressive utterance in the status update on media social twitter is expressing learning feeling, expressing anger feeling, expressing welcoming, expressing congratulating, expressing tiredness, expressing hoping, expressing happiness, expressing love, expressing thanking, expressing sadness, expressing sorrow, expressing worrying, expressing like, expressing dislike, expressing condolence, expressing apologizing, expressing pleasure, expressing longing and expressing shock.